1994
DOI: 10.5271/sjweh.1417
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cardiac risk among professional drivers.

Abstract: of cardiac risk among profe ssional drivers. Scand J Work Environ Health 1994;20:73-86.This literature review indicates that professional drivers have excess cardiac risk that is not fully explained by standard risk factors. The contributi on of occupation is suggested by two independent methods and by psychophysiological studies during on-the-job driving. Driving has been conceptualized as a threat-avoidance task. Stimuli encountered in traffic are not inherently aversive but become so by association with dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 84 publications
0
48
0
Order By: Relevance
“…Since then, research has shown that the excess risk in cardiovascular disease among urban bus drivers is not experienced by rural bus drivers, and, for urban bus drivers, is independent of both leisure-time physical activity and occupational Krause et al physical activity (80,81). Instead the excess risk is now thought to be attributable to the high levels of job stress experienced by urban bus drivers (82)(83)(84)(85), a factor that may have confounded the reported association with sedentary work (5,21). Clearly, the lack of control for psychosocial job factors in most previous studies of occupational physical activity is a major limitation of the literature.…”
Section: Comparison With Other Studies and Known Risk Factorsmentioning
confidence: 99%
“…Since then, research has shown that the excess risk in cardiovascular disease among urban bus drivers is not experienced by rural bus drivers, and, for urban bus drivers, is independent of both leisure-time physical activity and occupational Krause et al physical activity (80,81). Instead the excess risk is now thought to be attributable to the high levels of job stress experienced by urban bus drivers (82)(83)(84)(85), a factor that may have confounded the reported association with sedentary work (5,21). Clearly, the lack of control for psychosocial job factors in most previous studies of occupational physical activity is a major limitation of the literature.…”
Section: Comparison With Other Studies and Known Risk Factorsmentioning
confidence: 99%
“…It shows that the prolonged weekly exposure to driving takes its toll. As other studies have shown, the high risk of this occupation is not restricted to low back injuries, but also includes cardiovascular and gastrointestinal disease [Winkleby et al, 1988;Albright et al, 1992;Belkic et al, 1994;Evans, 1994;Tüchsen and Endahl, 1999]. A review of research on health problems among bus drivers stated that ''it is usually not possible for transit operators to work full-time in their profession throughout their occupational career'' [Tränkle and Bailer, 1996].…”
Section: Weekly Driving Hoursmentioning
confidence: 99%
“…Since then research has shown that the excess risk in CVD among urban bus drivers is not experienced by rural bus drivers, and, among urban bus drivers, is independent of both LTPA and OPA (35,36). Instead the excess risk is now thought to be attributable to the high levels of job stress experienced by urban bus drivers (37)(38)(39)(40), a factor that may have confounded the reported association with sedentary work (8,16). Clearly, exposure misclassification and lack of control for psychosocial job factors are major limitations of most studies.…”
mentioning
confidence: 99%